2018
DOI: 10.1038/s41598-018-27185-8
|View full text |Cite
|
Sign up to set email alerts
|

Human influence on sub-regional surface air temperature change over India

Abstract: Human activities have been implicated in the observed increase in Global Mean Surface Temperature. Over regional scales where climatic changes determine societal impacts and drive adaptation related decisions, detection and attribution (D&A) of climate change can be challenging due to the greater contribution of internal variability, greater uncertainty in regionally important forcings, greater errors in climate models, and larger observational uncertainty in many regions of the world. We examine the causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…The surface air temperature changes over India between 1956 and 2005 are attributed to anthropogenic forcing mostly by greenhouse gases and partially offset by other anthropogenic forcings including aerosols and land use land cover change (Dileepkumar et al 2018). The observed changes in maximum temperature during the post-monsoon and minimum temperature during the pre-monsoon and monsoon seasons in South India during 1950-2005 are assessed to be detectably different from natural internal climate variability, and these temperature changes are attributed with confidence to climate change induced by anthropogenic effects (Sonali et al 2018).…”
Section: Causes Of Observed Changesmentioning
confidence: 99%
“…The surface air temperature changes over India between 1956 and 2005 are attributed to anthropogenic forcing mostly by greenhouse gases and partially offset by other anthropogenic forcings including aerosols and land use land cover change (Dileepkumar et al 2018). The observed changes in maximum temperature during the post-monsoon and minimum temperature during the pre-monsoon and monsoon seasons in South India during 1950-2005 are assessed to be detectably different from natural internal climate variability, and these temperature changes are attributed with confidence to climate change induced by anthropogenic effects (Sonali et al 2018).…”
Section: Causes Of Observed Changesmentioning
confidence: 99%
“…Although the definition of a heat wave is not unique, they comprise, most generally, of episodes of consecutive days with above normal high temperatures (Perkins et al ., 2012). Recent studies have investigated heat wave characteristics in India and observed changes therein (Pai et al ., 2013; Murari et al ., 2016; Ratnam et al ., 2016; Rohini et al ., 2016; Mazdiyasni et al ., 2017; Panda et al ., 2017; Sharma & Mujumdar, 2017; Dileepkumar et al ., 2018; Sandeep & Prasad, 2018; Van Oldenborgh et al ., 2018) or future projections thereof (Murari et al ., 2015; Im et al ., 2017; Mishra et al ., 2017). Others (Wehner et al ., 2016; Pattanaik et al ., 2017; Gouda et al ., 2017; Ghatak et al ., 2017; Van Oldenborgh et al ., 2018; Dodla et al ., 2017; Chandran et al ., 2017; Nair et al ., 2017) study particular heat wave episodes focusing mainly on the 2015 heat wave event that resulted in more than 2000 deaths in India.…”
Section: Introductionmentioning
confidence: 99%
“…These changes are on account of anthropogenic GHG and aerosol forcings, and changes in land use and land cover (e.g. Krishnan and Ramanathan 2002;Dileepkumar et al 2018).…”
Section: Synthesis Of Regional Climate Changementioning
confidence: 99%
“…The annual mean near-surface air temperature over India has warmed by around 0.7°C during 1901-2018 (Srivastava et al 2019), with the post-1950 trends attributable largely to anthropogenic activities (Dileepkumar et al 2018) (High confidence). Atmospheric moisture content over the Indian region has also risen during this period (Krishnan et al 2016;Mukhopadhyay et al 2017;Mukherjee et al 2018) (High confidence).…”
Section: Synthesis Of Regional Climate Changementioning
confidence: 99%